Preparation Optimization and Performance Evaluation of Waterborne Epoxy Resin for Roads - Fei Wang; Hao Fu; Guixiang Liu; Chaohui Wang; Sixin Yu (Advances in Civil Engineering)
To further improve the road performance of waterborne epoxy resin, it was prepared by using the phase inversion method. The tensile properties, bending properties, impact resistance, and storage stability of waterborne epoxy resin were determined. The bonding properties of waterborne epoxy resin were analyzed. At the same time, their properties were compared with those of waterborne epoxy resin prepared by using the curing agent emulsification method. The performance of waterborne epoxy resin was comprehensively evaluated based on multi-index grey target decision model. The results show that the optimum preparation parameters for the preparation of waterborne epoxy resin by phase inversion method are shear time 1.5 h, shear temperature 60°C, and shear rate 1300–1500 r/min. The suitable contents of emulsifier A and B are 18% and 16%, respectively. The tensile strength, elongation at break, bending strength, bending deformation, and impact strength of waterborne epoxy resin prepared by emulsifier A can reach 34.46 MPa, 12.96%, 85.37 MPa, 19.42 mm, and 15.66 kJ/m2, respectively. It shows improved mechanical strength, deformation ability, impact resistance, and bonding performance. The comprehensive properties of waterborne epoxy resin prepared by emulsifier A are the best. It is suggested to use phase inversion method to prepare waterborne epoxy resin for roads.